2016
DOI: 10.4025/actascianimsci.v38i2.29030
|View full text |Cite
|
Sign up to set email alerts
|

<b>The quality of silage of different sorghum genotypes

Abstract: The objective was to select from among 24 sorghum genotypes the superior ones for silage production. The study was conducted in the experimental field of Embrapa Maize & Sorghum, in the municipality of Sete Lagoas, Minas Gerais State. It used 24 forage sorghum genotypes, 21 being hybrids from the crossing of grain sorghum females and forage males (12F38019, 12F38006, 12F40006, 12F40005, 12F40019, 12F37016, 12F37005, 12F37043, 12F39006, 12F39005, 12F39019, 12F38005, 12F38007, 12F37007, 12F39007, 12F40007, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
3
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 23 publications
3
15
3
9
Order By: Relevance
“…Tolentino et al (2016) reported values of 37.12% for sorghum of Volumax and 39.48% DM for BRS610, with values higher than those found in the present experiment for the same genotypes.…”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…Tolentino et al (2016) reported values of 37.12% for sorghum of Volumax and 39.48% DM for BRS610, with values higher than those found in the present experiment for the same genotypes.…”
Section: Resultscontrasting
confidence: 54%
“…Thus, the low nitrogen content of silages is a limiting factor for the use of forage of these genotypes mainly for animals with high nutritional requirements. Tolentino et al (2016) found CP content above 9.06% when evaluated silages of twenty-four different genotypes of sorghum, values higher than those presented in this study.…”
Section: Resultscontrasting
confidence: 53%
“…In regard to the water activity, the lower values observed in the silages with banana peel can be explained by the higher dry matter content of the banana peel (89.67% -Table 1), since according to Tolentino et al (2016), as the addition of solutes in silages occurs, the lower the water activity will be.…”
Section: Resultsmentioning
confidence: 99%
“…The ammoniacal nitrogen (N-NH 3 ) was also quantified in the broth, by distillation with magnesium oxide and calcium chloride, using boric acid solution and 1980). One sample of the silage was collected to determine the water activity (AW) using the AquaLab 4TE DUO equipment (Tolentino et al, 2016). The remaining silage from each silo was pre-dried in a forced ventilation oven at 55°C for 72 hours.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, sorghum (Sorghum bicolor L) for silage, Buffel grass (Cenchrus ciliaris) for hay and cactus forage (Nopalea cochenillifera) are potential alternatives because they are tolerant to low rainfall, with considerable productive potential, easy to cultivate and nutritional value, being easy to grow (Cardoso et al, 2019;Tolentino et al, 2016).…”
Section: Introductionmentioning
confidence: 99%